Oxidative Stress Induces Skin Pigmentation in Melasma by Inhibiting Hedgehog Signaling - Nan-Hyung Kim; Ai-Young Lee (MDPI AG, 2023)
There is growing evidence that oxidative stress plays a role in melasma and disrupts primary cilia formation. Additionally, primary cilia have been suggested to have an inhibitory role in melanogenesis. This study examined the potential link between oxidative stress, skin hyperpigmentation, and primary cilia. We compared the expression levels of the nuclear factor E2-related factor 2 (NRF2), intraflagellar transport 88 (IFT88), and glioma-associated oncogene homologs (GLIs) in skin samples from patients with melasma, both in affected and unaffected areas. We also explored the roles of NRF2, IFT88, and GLIs in ciliogenesis and pigmentation using cultured adult human keratinocytes, with or without melanocytes. Our findings revealed decreased levels of NRF2, heme oxygenase-1, IFT88, and GLIs in lesional skin from melasma patients. The knockdown of NRF2 resulted in reduced expressions of IFT88 and GLI1, along with fewer ciliated cells. Furthermore, NRF2, IFT88, or GLI1 knockdown led to increased expressions in protease-activated receptor-2 (PAR2), K10, involucrin, tyrosinase, and/or melanin. These effects were reversed by the smoothened agonist 1.1. Calcium also upregulated these proteins, but not NRF2. The upregulation of involucrin and PAR2 after NRF2 knockdown was mitigated with a calcium chelator. In summary, our study suggests that oxidative stress in NRF2-downregulated melasma keratinocytes impedes ciliogenesis and related molecular processes. This inhibition stimulates keratinocyte differentiation, resulting in melanin synthesis and melanosome transfer, ultimately leading to skin hyperpigmentation.